Effect of Salinity Stress on Germination, Seedling Growth, Mineral Uptake and Chlorophyll Contents of Three Cucurbitaceae Species - Naseer, Muhammad Noman; Rahman, Faiz Ur; Hussain, Zahoor; Khan, Irshad Ahmad; Aslam, Muhammad Muzammal; Aslam, Ali; Waheed, Hasnain; Khan, Asad Ullah; Iqbal, Shahid (Brazilian Archives of Biology and Technology, 2022)
Abstract This study was performed to screen out the various species of ‘Cucurbitaceae’ family, musk melon (Kalash and Durga), bottle gourd (Crystal Long and Nuefield) and squash (Green Round, and Squash Malika) against the salt stress. All genotypes were treated with five different levels of NaCl (T0 = control, T1 = 1.5 dS m-1, T2 = 3.0 dS m-1, T3 = 4.5 dS m-1 and T4 = 6.0 dS m-1) and half strength of Hoagland’s nutrients solution as the base nutrient solution. Results showed that the bottle gourd varieties “Nuefield” and “Crystal Long” performed best by maintaining the highest germination (93.2% and 85.6%), number of leaves per plant (4.5 and 5.7), shoot length (16.84 cm and 16.14 cm), root length (13.48 cm and 13.00 cm), plant fresh weight (942.2 g and 918.6 g), plant dry weight (118.4 g and 107.5 g), leaf area (171.2 cm2 and 169.1 cm2), chlorophyll content (3.5 μg/cm-2 and 3.4 μg/cm-2) with low chloride (1.57 ppm and 1.59 ppm) and sodium content (0.47 ppm and 0.51 ppm) under salt stress followed by varieties of Squash (Green Round, and Squash Malika) and musk melon (Kalash and Durga). It was also found that a higher level of salinity (4.5 dS m-1 and 6.0 dS m-1) has more adverse effects on the performance of all selected genotypes. Conclusively, it can be recommended that as compared to all tested species, bottle gourd varieties “Nuefield” and “Crystal Long” have the ability to withstand against salinity stress and should be planted under salt stress conditions.